(untitled) (American Journal of Islam and Society, 2025)
As a result of modernity and the emergence of gender studies, Islamic texts that discuss women and their status in Islam’s broader world-view have been revisited and re-interpreted. Traditional modes of interpretations and cosmologies have been questioned and re-interpretations have been attempted. Modern subcontinental tafsīr literature has also experienced the impact of modernity, which in turn has led to the production of exegetical trends of a diverse and competing nature. Against this backdrop, this article takes up Q.4:34 as a case study because it is one of the most contested of these texts. The article critically evaluates some of the most significant and impactful Urdū exegetical trends in the literature of the modern subcontinent and analyze their methods and conclusions in relation to Q.4:34. This analysis provides us with a greater appreciate of the dynamics of textual authority, text reception and exegetes’ role in the process of meaning making. The article deliberates upon an important yet unexplored modern subcontinent exegetical trends, and attempts to fill the gap in context of Q.4:34.